5th International Workshop on Speech Processing in Everyday Environments (CHiME 2018) 2018
DOI: 10.21437/chime.2018-8
|View full text |Cite
|
Sign up to set email alerts
|

Front-end processing for the CHiME-5 dinner party scenario

Abstract: This contribution presents a speech enhancement system for the CHiME-5 Dinner Party Scenario. The front-end employs multi-channel linear time-variant filtering and achieves its gains without the use of a neural network. We present an adaptation of blind source separation techniques to the CHiME-5 database which we call Guided Source Separation (GSS). Using the baseline acoustic and language model, the combination of Weighted Prediction Error based dereverberation, guided source separation, and beamforming redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 105 publications
(101 citation statements)
references
References 23 publications
(27 reference statements)
0
101
0
Order By: Relevance
“…GSS enhancement is a blind source separation technique originally proposed in [14] 1 to alleviate the speaker overlap problem in CHiME-5. Given a mixture of reverberated overlapped speech, GSS aims to separate the sources using a pure signal processing approach.…”
Section: Guided Source Separationmentioning
confidence: 99%
See 4 more Smart Citations
“…GSS enhancement is a blind source separation technique originally proposed in [14] 1 to alleviate the speaker overlap problem in CHiME-5. Given a mixture of reverberated overlapped speech, GSS aims to separate the sources using a pure signal processing approach.…”
Section: Guided Source Separationmentioning
confidence: 99%
“…Those masks are also given by the mentioned class affiliations. For the single array (CHiME-5) track, simulations have shown that multiplying the beamformer output with the target speaker mask improves the performance on the U data, but the same approach degrades the performance in the multiple array track [14]. This is because the spatial selectivity of a single array is very limited in CHiME-5: the speakers' signals arrive at the array, which is mounted on the wall at some distance, at very similar impinging angles, rendering single array beamforming rather ineffective.…”
Section: Guided Source Separationmentioning
confidence: 99%
See 3 more Smart Citations